2020
DOI: 10.22492/ije.8.4.05
|View full text |Cite
|
Sign up to set email alerts
|

Academic Failure: Unspoken Experiences by International Postgraduate Students in a Malaysian University

Abstract: Malaysia aspires to become a regional and international hub of higher education through an international student mobility initiative. Existing scholarly work on international students is skewed towards understanding the general challenges faced by international students, but limited work has been conducted in exploring the impact of severe supervision challenges on international postgraduate students’ experiences in a Malaysian research university. Hence, this paper explores the evidence of academic failure ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…This is consistent with the previous research that emphasizes a time-based con ict when employees overprioritize one role over another (Culbertson et al, 2011). Notwithstanding this, underquali ed faculty may also be deleterious to student progress as they lack the skills and competence to correctly direct their students to appropriate literature that can help the students comfortably handle their research (Gao, 2019;Singh, 2020).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is consistent with the previous research that emphasizes a time-based con ict when employees overprioritize one role over another (Culbertson et al, 2011). Notwithstanding this, underquali ed faculty may also be deleterious to student progress as they lack the skills and competence to correctly direct their students to appropriate literature that can help the students comfortably handle their research (Gao, 2019;Singh, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…They will, therefore, prefer to be handled by a highly quali ed member of faculty because they believe that such individuals have the expertise in their discipline to take them through research guidance (Khozaei et al, 2015). Scholars postulate that many students will not perform well when their teachers or professors do not possess adequate expertise, knowledge, skills, and attitudes (Khozaei et al, 2015;Singh, 2020). This quali cation encompasses formal certi cation and credentials, and all psychosocial and linguistic aspects (Gobel et al, 2013;Sidhu et al, 2014) that enhance effectiveness and e ciency since student success is a result of the quality of the process of teaching and learning (Revisi and Lamas, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Sustainable supervisory relationships were perceived by both stakeholders in terms of establishing future employment rapport, enhancing research collaboration opportunities upon graduation and heightening global engagement via networking initiatives. These findings present a quite different scenario from those in Singh (2020a), that supervisors and supervisees usually focus on the relationship of supervision as a short-term relationship, which only occurs during the period of research candidature. This invites further reflection and study as to reasons.…”
Section: Discussionmentioning
confidence: 57%
“…These benefits are only achievable if there are quality supervision relationships established between supervisors and supervisees during studies, as suggested by Singh (2018). Because Malaysia is a relatively new contender in providing international education, the literature around postgraduate international students’ supervision is limited in exploring supervisors’ roles (Sidhu et al , 2014), supervision challenges (Ismail et al , 2013; Sidhu et al , 2014) and effective supervision strategies (Singh, 2020a). Moreover, to the best of the author’s knowledge, there is no one study that has explored international students’ and staff members’ experiences on sustainable supervisor relationships upon graduation in a non-Western country such as Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…They will, therefore, prefer to be handled by a highly quali ed member of faculty because they believe that such individuals have the expertise in their discipline to take them through research guidance (Khozaei et al, 2015). Scholars postulate that many students will not perform well when their teachers or professors do not possess adequate expertise, knowledge, skills, and attitudes (Khozaei et al, 2015;Singh, 2020). This quali cation encompasses formal certi cation and credentials, and all psycho-social and linguistic aspects (Gobel et al, 2013;Sidhu et al, 2014) that enhance effectiveness and e ciency since student success is a result of the quality of the process of teaching and learning (Revisi and Lamas, 2015).…”
Section: Discussionmentioning
confidence: 99%